Initiating technical refinements in high-level golfers: Evidence for contradictory procedures. Issue 4 (18th May 2016) - Carson, Howie J.; Collins, Dave; Richards, Jim
Abstract: When developing motor skills there are several outcomes available to an athlete depending on their skill status and needs. Whereas the skill acquisition and performance literature is abundant, an under-researched outcome relates to the refinement of already acquired and well-established skills. Contrary to current recommendations for athletes to employ an external focus of attention and a representative practice design, Carson and Collins' (2011) [Refining and regaining skills in fixation/diversification stage performers: The Five-A Model. International Review of Sport and Exercise Psychology, 4, 146–167. doi:10.1080/1750984x.2011.613682 ] Five-A Model requires an initial narrowed internal focus on the technical aspect needing refinement: the implication being that environments which limit external sources of information would be beneficial to achieving this task. Therefore, the purpose of this paper was to (1) provide a literature-based explanation for why techniques counter to current recommendations may be (temporarily) appropriate within the skill refinement process and (2) provide empirical evidence for such efficacy. Kinematic data and self-perception reports are provided from high-level golfers attempting to consciously initiate technical refinements while executing shots onto a driving range and into a close proximity net (i.e. with limited knowledge of results). It was hypothesised that greater control over intended refinements would occur when environmental stimuli were reduced in the most unrepresentative practice condition (i.e. hitting into a net). Results confirmed this, as evidenced by reduced intra-individual movement variability for all participants' individual refinements, despite little or no difference in mental effort reported. This research offers coaches guidance when working with performers who may find conscious recall difficult during the skill refinement process.